2021
DOI: 10.7759/cureus.14958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin B6, B9, and B12 Supplementation on Homocysteine Level and Cardiovascular Outcomes in Stroke Patients: A Meta-Analysis of Randomized Controlled Trials

Abstract: Globally, stroke is the fifth-most leading cause of mortality and also the third leading cause of disability. This study aimed to assess the effect of vitamin B 6 , B 9 , and B 12 supplementation on homocysteine level, risk of stroke, cardiovascular disorders, and vascular death among stroke participants. An extensive literature search was done through PubMed, Medline, Embase, and Clinical key database from 1 January 2000 to 1 January 2020. Effect of vitamin B (B 6 , B 9 , and B 12 ) supplementation on homocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
1
19
0
2
Order By: Relevance
“…Many studies have shown that hyperhomocysteinemia is an independent risk factor for cerebral infarction and atherosclerosis (Ganguly & Alam, 2015; Poddar, 2021; T. Zhang et al., 2020). Vitamin B supplementation therapy including vitamin B6, B12, and folic acid, especially in stroke patients, can effectively reduce HCY levels, thereby reducing the risk and recurrence of ischemic stroke (X. Huang et al., 2017; Kataria et al., 2021; Li et al., 2016; Yuan et al., 2021). The mechanisms underlying the relationship of elevated HCY levels and PSD have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that hyperhomocysteinemia is an independent risk factor for cerebral infarction and atherosclerosis (Ganguly & Alam, 2015; Poddar, 2021; T. Zhang et al., 2020). Vitamin B supplementation therapy including vitamin B6, B12, and folic acid, especially in stroke patients, can effectively reduce HCY levels, thereby reducing the risk and recurrence of ischemic stroke (X. Huang et al., 2017; Kataria et al., 2021; Li et al., 2016; Yuan et al., 2021). The mechanisms underlying the relationship of elevated HCY levels and PSD have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, hyperhomocysteinemia is also considered to be highly associated with ischemic stroke. Meanwhile, some studies have indicated that reducing HCY levels by supplementing vitamin B including vitamin B6, B12, and folic acid can reduce the risk of ischemic stroke (X. Huang et al., 2017; Kataria et al., 2021; Li et al., 2016). Previous studies have reported that elevated serum levels of HCY at admission were associated with PSD at 3 months to 1 year after stroke (Cheng et al., 2018; Li et al., 2017; Pascoe et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, elevated cholesterol and triglycerides level for a chronic period leads to increased endothelial permeability and causes accumulation of lipoproteins. Further these lipoproteins are oxidized as a result of increased free radical level [18].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reported that vitamin B supplementations that reduced Hcy prevented the combined risk of stroke, myocardial infarction, and vascular death among stroke patients. 6 …”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis reported that vitamin B supplementations that reduced Hcy prevented the combined risk of stroke, myocardial infarction, and vascular death among stroke patients. 6 However, many of the previous researches have been limited to ischemic stroke, and few published studies are available concerning hemorrhagic stroke. Globally, acute spontaneous intracerebral hemorrhage (ICH) accounts for approximately 25% of all stroke cases.…”
Section: Introductionmentioning
confidence: 99%